Strategic Program Management of Research-Based Madrasahs in Cultivating a Research-Oriented Learning Culture - Ainun, Alfia; Imaduddin, Muhammad; Masturin; Az Zafi, Ashif (JIEMAN: Journal of Islamic Educational Management, 2025)
The importance of an educational institution to innovate education in developing the quality of education amidst the needs of society through research programs.The research method used in this study is a qualitative approach with study. Data collection through access to the organization. observation, interview, and documentation. Testing the validity of data are triangulation. The data validation analysis techniques use in this research are data collection, data reduction, data presentation, and conclusions. Based o the research result,  it may be concluded that (1) Research madrasah plan in developing the research culture, are regulation of determine the purposes for research programs, designing resources, strength and barriers analysis and creating research program, and analyzes the advantages and disadvantages. (2) The research madrasah organization in developing the research culture, especially, establishment, design the team jobdesk. (3) The implementation of the research madrasah program in developing research culture. Consisted of socialization of the research program, the research course, which used the PJBL model, research tutoring, research supercamps, outing class, research training and MANSAKU Research science and social week (MSW). Those activities are reflected as the character of observed behavioral regularities. (4) The research madrasah supervision in developing research culture are consisted of determine of work standard, performance assessment and irregularities improvements formed in a creation.